Development of an automated on-chip bead-based ELISA platform - Campbell, Jennifer (Anal Methods, 2015)
We present a lab-on-a-chip and associated instrument for heterogeneous enzyme-linked immunosorbent assay (ELISA)-based detection of proteins from liquid samples. The system performs all necessary ELISA steps (starting from antigen incubation) in a quarter of the time required for corresponding plate-based protocols. We have previously described the instrument, which automates fluidic control via remote valve switching and detects fluorescence from reacted substrate, for use in a molecular diagnostics application. The ELISA chip reported here utilizes a high surface area bead bed to enhance capture efficiency and increase the dynamic range of the assay as compared to a standard plate-based ELISA. Its functionality is demonstrated using human IL-10 as a model antigen, but theoretically any sandwich ELISA could be ported onto this “open source platform.” We show that our automated on-chip assays have greater sensitivities than the corresponding standard manual plate-based ELISAs, and that single samples can be assayed in a fraction of the time.